PENGARUH SELF EFFICACY DAN EMOTIONAL STABILITY TERHADAP CORPORATE SUSTAINABILITY DENGAN SISTEM PENGENDALIAN INTERN SEBAGAI VARIABEL MODERASI - Karmila Malik; Jamaluddin Majid; Suhartono Suhartono (ISAFIR: Islamic Accounting and Finance Review, 2022)
This study aims to determine the effect of self-efficacy and emotional stability on corporate sustainability with an internal control system as a moderating variable at PT. Suracojaya Abadi Motor Yamaha Makassar. This research is a quantitative research with associative research approach.The population in this study is the company PT.Suracojaya Abadi Motor Yamaha Makassar using data collection methods with sample techniques. The number of samples in this study were 120 respondents, while the samples in this study were employees of PT. Suracojaya Abadi Motor Yamaha Makassar. The data analysis technique used is multiple linear regression analysis.The results of the analysis show that self-efficacy and emotional stability have a significant positive effect on corporate sustainability and the internal control system moderates the effect of self-efficacy and emotional stability on corporate sustainability.